Cytotoxicity and mechanisms of action of Zerumbone-loaded nanostructured lipid carrier in triple negative breast cancer cells, MDA-MB-231 - Hosseinpour, Mahnaz (2015)
Breast cancer is a life-threatening disease mostly effecting women. According to the Malaysian National Cancer Registry (2006), breast cancer is one of the five most common cancers amongst Malaysian women. Currently, the most widely used breast cancer therapies include surgery, chemotherapy, radiotherapy, hormonal therapy and targeted therapy. Generally, most of these treatments can affect normal cells and tissues with several side effects. Therefore, scientists are applying new techniques and strategies, including the use of natural products in drug discovery for enhanced survival rates with fewer side effects. Zerumbone (ZER), a monocyclic, sesquiterpene crystalline compound, was isolated from a ginger herb, Zingiber zerumbet (L.) Smith, locally known as lempoyang. Several studies had demonstrated that ZER has the ability to inhibit abnormal proliferation of neoplastic colon, cervical, ovary, liver, breast and blood cells. In addition, ZER demonstrated selective antiproliferative effect towards cancer cells. Unfortunately, ZER is poorly soluble in water that leads to poor oral bioavailability and hence, delivery. For this reason, it is crucial to improve the delivery of this compound in blood by incorporation into nanostructured lipid carrier (ZER-NLC), which increases its water solubility. This study determined and compared the cytotoxicity of ZER-NLC with ZER towards triple negative breast cancer, MDA-MB-231, cells. The IC50 of ZER and ZER-NLC on MDA-MB-231 cells were determined by 3-(4, 5-dimethylthiazol-2-yl) -2, 5-diphenyltetrazolium bromide assay. Mode of cell death was determined by microscopic observation of AO/PI double stained cells, annexin-V, TUNEL, caspases assays and cell cycle analysis. In addition, Western blot was used to determine the expression of Bcl-2, Bcl-xL, Bax, cytochrome c (Cyt-c) and proliferation cell nuclear antigen (PCNA) proteins. ZER and ZER-NLC significantly (P < 0.05) decreased the proliferation of MDAMB-231 cells in a time-dependent manner. The IC50 of ZER and ZER-NLC on the MDA-MB-231 cells at 72 hours, were 5.96 ± 0.13 and 6.01 ± 0.11 µg/mL, respectively. Both ZER and ZER-NLC caused development of apoptotic features in MDA-MDB-231 cells, particularly nuclear condensation, cell shrinkage, chromatin cleavage and membrane blebbing. Treatment with ZER and ZER-NLC caused MDA-MB-231 cell cycle arrest at G2/M phase. Furthermore, annexin-V and tunnel assay also demonstrated that both ZER and ZER-NLC induced apoptosis in MDA-MB-231 cells. ZER and ZER-NLC induced apoptosis via intrinsic (mitochondrial) pathway through the activation of caspase-3 and caspase- 9. The western blot analysis provided evidence of up-regulation of Bax, Cyt-c with down-regulation of Bcl-2, Bcl-xL and PCNA proteins in both ZER- and ZERNLC-treated MDA-MB-231 cells. Finally, ZER and ZER-NLC treatment did not affect the proliferation of non-cancerous breast epithelial cells (MCF-10A), suggesting that they are cancer-cell specific. In conclusion, the current study showed that the cytotoxic effect of ZER-NLC in the induction of apoptosis similar to that of ZER. Thus, NLC can be used as a carrier for ZER in the treatment of breast cancers.